Mass Spectrometry Directed Pre-Clinical Studies of Asthma Candidate MIDD0301 and Its Analogs - (:unkn) unknown (My University, 2021)
ABSTRACTMASS SPECTROMETRY DIRECTED PRE-CLINICAL STUDIES OF ASTHMA CANDIDATE MIDD0301 AND ITS ANALOGS by Md Shadiqur Rashid Roni The University of Wisconsin-Milwaukee, 2021 Under the Supervision of Professor Alexander (Leggy) Arnold Asthma is one of the most prevalent global health problems. More than 25 million Americans are suffering from asthma and their symptoms especially in children are not well controlled with current medications. The current therapeutic options to control symptoms are limited and are commonly based on inhaled corticosteroids. There are several reasons for uncontrolled asthma symptoms that includes steroid resistance, improper use of inhalers and very few orally available medications. Thus, there is an unmet medical need for a novel non-steroidal oral asthma medication. To address this issue, our research group is targeting the amino butyric acid type A receptors (GABAAR) in the lung using two strategies. First of all, subtypes selective compounds, exploiting the fact that the expression of GABAARs subtypes differ between the central nervous system (CNS) and peripheral tissue. Secondly, GABAAR ligands with the inability to cross the blood brain barrier (BBB) to reduce CNS exposure. The objective of our current studies was to characterize our asthma lead compound MIDD0301 in respect to physicochemical properties, pharmacokinetics, and metabolism.Many in vitro and in vivo assays were designed and successfully implemented to better understand the pharmacokinetics and pharmacodynamics of MIDD0301. Most investigations included the use of liquid chromatography tandem mass spectrometry to analyze complex biological samples such as blood, tissue, urine and feces. Several preparation, extraction, purification, and clean-up procedures were developed and optimized to achieve our objective. Additionally, we were able to determine aqueous solubility, permeability, lipophilicity and pKa to understand the in vivo behavior of MIDD0301. The two major findings were: a) a suitable aqueous formulation that provided the best oral bioavailability and b) by studying the kinetics of a seven-membered ring-opening reaction in acidic conditions, it was found that the in vivo interconversion neither affects the original stereochemistry of MIDD0301 nor its bioavailability. Favorable physicochemical properties encouraged us to develop a scalable synthesis for MIDD0301. The manufacturing processes of a lead compounds become especially important when the NCE (new chemical entity) is part of an IND (investigational new drug) application. To support the analysis of such a process, two reverse phase and three normal phase chromatographic methods were optimized to determine purity and optical purity. Next, we evaluated drug metabolism and pharmacokinetics study (DMPK), which included metabolite identification and characterization of the metabolic excretion profile. We were able to measure absorption, distribution, metabolism, and excretion and found that MIDD0301 is absorbed quickly and did not undergo phase I biotransformation. MIDD0301 was found in urine and feces and underwent phase II conjugation by forming glucuronide, glucoside, and taurine conjugates. MIDD0301 glucuronide was identified as the main metabolite. A comparative study of MIDD0301 enantiomers showed similar binding affinities and PKPD properties that differed in the ability of form the glucoside conjugate. At the same time, we continued to explore new asthma candidates that unlike MIDD0301 formed a neutral species at physiological pH but were still unable to cross the BBB. Substituted analogs of MIDD0301 bearing long hydrophobic chains are now being evaluated with the goal to achieve long-acting property and limited phase II conjugation.
Keywords: Asthma; DMPK; ADMET; Glucuronide; Glucoside; Taurine conjugate; Mass spectrometry; LC/MS/MS; physicochemical properties; Pre-clinical study